Evolution: sperm ejection near and far. - Pizzari, T (2004)
In promiscuous fruit flies, the last male to inseminate a female has a fertilising advantage. Recent evidence indicates that this happens because females eject previously stored semen after a new copulation, revealing female bias in sperm use and the resulting battle of the sexes over fertilisation.